2018
DOI: 10.1080/19932820.2018.1500346
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the MST1-JNK signaling pathway in apoptosis of colorectal cancer cells induced by Taurine

Abstract: The aim of this study was to observe the impact of the mammalian sterile 20-like kinase 1-c-Jun N-terminal kinase (MST1-JNK) signaling pathway on apoptosis in colorectal cancer (CRC) cells induced by Taurine (Tau). Caco-2 and SW620 cells transfected with p-enhanced green fluorescent protein (EGFP)-MST1 or short interfering RNA (siRNA)-MST1 were treated with Tau for 48 h. Apoptosis was detected by flow cytometry, and the levels of MST1 and JNK were detected by western blotting. Compared with the control group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…JNK is mainly localized in the cytoplasm. When activated, partially activated JNK translocating into the nucleus activates intranuclear transcription factors, such as c-Jun, ATF2, and p53, by phosphorylation [2830], thus enhancing the expression of downstream apoptosis-related genes and promoting apoptosis [20, 49]. In this study, our results reveal that treatment with high glucose resulted in a marked reduction of p-JNK.…”
Section: Discussionmentioning
confidence: 68%
“…JNK is mainly localized in the cytoplasm. When activated, partially activated JNK translocating into the nucleus activates intranuclear transcription factors, such as c-Jun, ATF2, and p53, by phosphorylation [2830], thus enhancing the expression of downstream apoptosis-related genes and promoting apoptosis [20, 49]. In this study, our results reveal that treatment with high glucose resulted in a marked reduction of p-JNK.…”
Section: Discussionmentioning
confidence: 68%
“…On the one hand, JNK contributes to cancer cell apoptosis. JNK signaling plays crucial roles in taurine-induced apoptosis of colorectal cancer cells [20]. Further, endoplasmic reticulum stress induced interaction of JNK with mitochondrial SH3BP5, leading to impaired respiration and increased mitochondrial ROS, sustaining JNK activation culminating in apoptosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the molecular mechanisms of taurine in more depth, taurine suppressed p53 -/tumor cells more efficiently than p53 +/+ tumor cells, indicating that the apoptosis-stimulatory action of taurine is the consequence of not only mitochondrial apoptotic pathway but also of multiple signaling pathways in colon cancer cells. In support, Liu et al (43) have shown that the mammalian sterile 20-like kinase 1-c-Jun N-terminal kinase (MST1-JNK) signaling pathway was essential for taurine-induced apoptosis in colon cancer cells (Caco-2 and SW620 cells). Following the treatment of colon cancer cells with taurine, the JNK signaling cascade was activated, either by transmitting direct signals to the MST1 target gene or by controlling the action of MST1 target via a feedback mechanism, with the ultimate aim of inducing apoptosis (43).…”
Section: Beneficial Effect Of Taurine In Various Cancers (In Vitro Anmentioning
confidence: 93%
“…In support, Liu et al (43) have shown that the mammalian sterile 20-like kinase 1-c-Jun N-terminal kinase (MST1-JNK) signaling pathway was essential for taurine-induced apoptosis in colon cancer cells (Caco-2 and SW620 cells). Following the treatment of colon cancer cells with taurine, the JNK signaling cascade was activated, either by transmitting direct signals to the MST1 target gene or by controlling the action of MST1 target via a feedback mechanism, with the ultimate aim of inducing apoptosis (43). Importantly, the growth-inhibitory effect of taurine was also proved either in colitis-model induced by TNBS (16) or in another colitis-inducible model caused by DSS (24).…”
Section: Beneficial Effect Of Taurine In Various Cancers (In Vitro Anmentioning
confidence: 93%
See 1 more Smart Citation